MENINGKATKAN KETERAMPILAN MOTORIK KASAR ANAK MELALUI PERMAINAN TRADISIONAL DENGAN LOMPAT TALI DI PAUD AN-NASHR - Siasmawati Siasmawati; Nur Hazizah; Rismareni Pransiska; Asdi Wirman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve the gross motor skills of early childhood children through the implementation of the traditional jump rope game at An-Nashr Early Childhood Education (PAUD). The background of this study is based on the low gross motor skills of children, such as motor coordination, balance, and jumping ability, where 55% of children have not achieved the expected development indicators. The method used is Classroom Action Research (CAR) which is implemented in two cycles, including the planning, implementation, observation, and reflection stages. The research subjects are 20 children. The methodology used for data collection includes observational and documentation techniques, while the analytical framework applied to the data adopts a qualitative descriptive methodology. The research findings show an increase in children's gross motor skills from cycle I to cycle II. In cycle I, the average achievement of children was 65%, while in cycle II it increased to 85%, resulting in an increase of 20%. This increase is seen in the indicators of jumping with balance, motor coordination, push-off, and landing. The results of this study indicate that conventional jump rope activities are effective in improving children's gross motor skills, while encouraging physical engagement, motivational learning, and social development among children.